Harley-Davidson : chasing a new generation of customers - Roese, Neal J., (SAGE knowledge. Cases., 2016)
Although Harley-Davidson had a record sales year in 2006 - and had maintained a commanding share of the heavyweight motorcycle market for the previous decade - it had become obvious that the company needed to take new action to sustain its growth. This study examines Harley-Davidson's drive to find a new generation of riders and a more diverse customer base.